Logic and reasonability of Internal Arbitration Award in view of Judicial Precedents - Eisa Amini; Abbas Mansoori (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2018)
The Legislator does not provide any specific structure and definition for awards in the context of domestic arbitration. However, Article 482 of Code of Civil Procedure emphasizes on the requirements of reasoning and justifiability in relation to arbitral awards. Therefore, from the wording of this article, it is implied that this issue is a basic element of arbitration award, and arbitrators have the same obligation as judges in this respect. Having said that, there is no specific rule defining what a reasoned and justifiable award means. Moreover, no sanction has been provided in the event of failing to meet these requirements. For this reason, doctrine and judicial cases are ambiguous. Some lawyers believe that the lack of these requirements would lead the award to be voidable. However, by making reference to article 489, others state that this matter is not a cause for voidability of award. Itseems that the lack of reasoned and justifiable contents may cause invalidity and voidability of award.